Investor sentiment, market timing and financial performance of Indonesian IPO firm - Tyasanto, Simforianus Arzak; Hapsari, Yudith Dyah; Hamid, Agustini (Trigin Publisher, 2024)
We investigated the impact of investor sentiment and market timing on firm financial performance on Initial Public Offering (IPO) stocks. We used cross-sectional regression of 106 IPO firms in Indonesia to analyze the factors that influenced initial public offerings (IPO) after the implementation of the acceleration board by Indonesian Stock Exchange in 2020. We used IPO data in 2019 as period before acceleration board implementation and 2020 for the first time implementation. Share turnover was proxy of investor sentiment while initial return was proxy of market timing. We also included size, asset growth, tangibility and profitability as independent variable. The finding offered that investor sentiment was found to have a influence towards firm performance but negative both in 2019 and 2020. Whereas market timing only influenced before accelaration board implemented, while other factors such as size, growth, tangibility of asset and profitability show mix results. After Indonesia Stock Exchange (IDX) implemented the acceleration board to open funding access through the capital market as a solution to the challenges faced by SMEs, It still did not have any track record of companies that are known to the public and the ease of recording requirements results in asymmetric information. The IPO funding only used to pay both short term and long term debt. The phenomenon influenced by investor sentiment because stock turnover could lead to increase stock performance and prove that high stock transaction in market did not guaranted that te stock would perfomed well.